Mutations in PRRT2 are not a common cause of infantile epileptic encephalopathies. Issue 5 (8th April 2013) - Heron, Sarah E.; Ong, Yeh Sze; Yendle, Simone C.; McMahon, Jacinta M.; Berkovic, Samuel F.; Scheffer, Ingrid E.; Dibbens, Leanne M.
Summary Heterozygous mutations in PRRT2 have recently been identified as the major cause of autosomal dominant benign familial infantile epilepsy (BFIE), infantile convulsions with choreoathetosis syndrome (ICCA), and paroxysmal kinesigenic dyskinesia (PKD). Homozygous mutations in PRRT2 have also been reported in two families with intellectual disability (ID) and seizures. Heterozygous mutations in the genes KCNQ2 and SCN2A cause the two other autosomal dominant seizure disorders of infancy: benign familial neonatal epilepsy and benign familial neonatal‐infantile epilepsy. Mutations in KCNQ2 and SCN2A also contribute to severe infantile epileptic encephalopathies (IEEs) in which seizures and intellectual disability co‐occur. We therefore hypothesized that PRRT2 mutations may also underlie cases of IEE. We examined PRRT2 for heterozygous, compound heterozygous or homozygous mutations to determine their frequency in causing epileptic encephalopathies (EEs). Two hundred twenty patients with EEs with onset by 2 years were phenotyped. An assay for the common PRRT2 c.649‐650insC mutation and high resolution‐melt analysis for mutations in the remaining exons of PRRT2 were performed. Neither the common mutation nor any other pathogenic variants in PRRT2 were detected in the 220 patients. Our findings suggest that mutations in PRRT2 are not a common cause of IEEs.